Branched benzothiadiazole-cored oligomers with terminal carbazoles: Synthesis and fluorescence probing nitroaromatics. (May 2015) - Peng, Jiang; Ye, Kaiqi; Sun, Jingbo; Zhan, Yong; Jia, Junhui; Xue, Pengchong; Zhang, Gonghe; Zhang, Zhenqi; Lu, Ran
Abstract: New branched benzothiadiazole-cored conjugated oligomers with terminal carbazoles1 and2 have been synthesized. It was found that no obvious shifts of the maximal absorption bands for1 and2 were detected in the films compared with those in solutions, indicating weak π-π stacking occurred in the solid states on account of site isolation effect of the branched architectures. Hence, the synthesized oligomers could emit strong red light in the films. Notably, the emission of the films based on1 and2 could be quenched obviously upon exposed to gaseous TNT and DNT. The fluorescence quenching efficiency of the oligomer2 -based film reached 91% when exposed to the saturated vapor of DNT for 3 min at 55 °C. The linear Stern–Volmer plot and the decrease of the fluorescence lifetime of2 induced by DNT suggested the fluorescence sensing mechanism was due to the photo-induced electron transfer. Graphical abstract: Highlights: New branched benzothiadiazole-cored conjugated oligomers with terminal carbazoles1 and2 have been synthesized. Weak π-π interaction occurs in the solid states of1 and2 due to site isolation effect of the branched architectures. The emission of the films based on1 and2 could be quenched obviously upon exposed to gaseous TNT and DNT.